2022
DOI: 10.1001/jamanetworkopen.2022.40993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maternal and Neonatal Antibody Levels After COVID-19 Vaccination vs SARS-CoV-2 Infection

Abstract: ImportancePregnant persons are at an increased risk of severe COVID-19 from SARS-CoV-2 infection, and COVID-19 vaccination is currently recommended during pregnancy.ObjectiveTo ascertain the association of vaccine type, time from vaccination, gestational age at delivery, and pregnancy complications with placental transfer of antibodies to SARS-CoV-2.Design, Setting, and ParticipantsThis cohort study was conducted in Pennsylvania Hospital in Philadelphia, Pennsylvania, and included births at the study site betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Vaccine-induced titers were found to be equivalent in pregnant, lactating, and non-pregnant women, suggesting that COVID-19 vaccines transfer antibodies both transplacental and through breast milk and provide context to the mechanisms behind which neonates can secure prolonged immunity. These new findings can be presented as tentative data for additional support for the acceptance of COVID-19 vaccinations in pregnant women [ 31 , 41 , 42 ].…”
Section: Effects Of Covid-19 Vaccines On Neonatal Viral Immunitymentioning
confidence: 86%
See 1 more Smart Citation
“…Vaccine-induced titers were found to be equivalent in pregnant, lactating, and non-pregnant women, suggesting that COVID-19 vaccines transfer antibodies both transplacental and through breast milk and provide context to the mechanisms behind which neonates can secure prolonged immunity. These new findings can be presented as tentative data for additional support for the acceptance of COVID-19 vaccinations in pregnant women [ 31 , 41 , 42 ].…”
Section: Effects Of Covid-19 Vaccines On Neonatal Viral Immunitymentioning
confidence: 86%
“…Though further research is required to identify the extent of this conclusion on humans, as well as its validity, the DART study is a major starting point for easing hesitancy in concerned pregnant patients. Additionally, a recent study found that mRNA vaccines are highly effective in the robust production of SARS-CoV-2-specific antibodies in pregnant women [ 31 , 40 , 41 , 42 ]. Vaccine-induced titers were found to be equivalent in pregnant, lactating, and non-pregnant women, suggesting that COVID-19 vaccines transfer antibodies both transplacental and through breast milk and provide context to the mechanisms behind which neonates can secure prolonged immunity.…”
Section: Effects Of Covid-19 Vaccines On Neonatal Viral Immunitymentioning
confidence: 99%
“…Efficiency of matAb transfer to pups, measured as dam:offspring IgG ratio, was ~ 0.57, which is similar to placental transfer ratios of SARS-CoV-2 matAbs in human mother-infant pairs in which the mother received a single dose of SARS-CoV-2 mRNA vaccine < 30 days prior to delivery. 23 Notably in humans, SARS-CoV-2 matAb levels have been shown to be higher after maternal vaccination compared to after maternal infection but maternal vaccination leads to slightly lower placental transfer ratios. 23 Further studies should evaluate if matAbs elicited by SARS-CoV-2 infections versus vaccinations have different inhibitory capacities in mouse models.…”
Section: Discussionmentioning
confidence: 98%
“…23 Notably in humans, SARS-CoV-2 matAb levels have been shown to be higher after maternal vaccination compared to after maternal infection but maternal vaccination leads to slightly lower placental transfer ratios. 23 Further studies should evaluate if matAbs elicited by SARS-CoV-2 infections versus vaccinations have different inhibitory capacities in mouse models.…”
Section: Discussionmentioning
confidence: 98%
“…Standard antenatal education should include vaccination needs, folic acid supplementation, smoking and alcohol cessation and optimising weight and nutritional status 52 53. COVID-19 and other vaccinations during pregnancy are safe and effective for the new born infants 54. Obstetric and/or maternofetal medicine input may be required for women with complex obstetric histories or comorbidities 49…”
Section: Appropriate Statementsmentioning
confidence: 99%